CHARACTERIZATION PHENOTYPE AND GENETIC DISTANCE SOME OF THE NATIVE CHICKEN STRAINS IN JAMBI PROVINCE INDONESIA - Depison; Gushairiyanto; Irmaya, Dika (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Characterization is used to determine genetic quality which is used as a basis for consideration in selection and crossing. The research materials were Super Chicken, Bangkok, KUB, Sentul, Kampung and Merawang. Data including qualitative and quantitative. Descriptive and quantitative qualitative data used t-test, T2-Hotelling test and principal component analysis. Data processing using Minitab and MEGA-X program. The results showed that body weight, weight gain and body size of Super chickens were significantly different (P<0.05) higher than the other chickens. The closest genetic distance between the lines is Kampung dan Sentul chicken, then between Bangkok and Super chicken. Sentul and Kampung chicken have a close relationship with KUB, compared to Bangkok, Super and Merawang. Conclusion: Qualitative criteria for Super, Bangkok, KUB, Sentul, and Kampung are still very diverse, while Merawang chickens are more uniform. The highest body weight up to the age of 4 months is Super chicken, followed by Bangkok, KUB, Sentul, Kampung and Merawang. The increase in the body weight of chickens is achieved at the age of 2-3 months.